OEA alleviates apoptosis in diabetic rats with myocardial ischemia/reperfusion injury by regulating the PI3K/Akt signaling pathway through activation of TRPV1 - Yao, Enhui; Luo, Lili; Lin, Chenxi; Wen, Jing; Li, Yanglongfei; Ren, Tong; Chen, Yujie; Huang, Jinhua; Jin, Xin (Frontiers in Pharmacology, 2022)
Reperfusion therapy after myocardial infarction may lead to myocardial injury, which can be complicated and exacerbated by diabetes. The existing therapeutic measures for myocardial ischemia-reperfusion injury (MIRI) in patients with diabetes are not ideal. Oleoylethanolamide (OEA) has been found to have protective effects on diabetes and acute cerebral ischemia. This study aimed to determine whether OEA can reduce MIRI in diabetic rat, and to explore the underlying mechanism. The model of diabetic rats with MIRI was established by blocking the left coronary artery for 30 min, followed by restoring blood flow stability for 120 min. The myocardial enzyme spectrum, area of MIRI, and expression levels of apoptosis-related proteins were detected. The results showed that OEA pretreatment could reduce myocardial infarction area, protect myocardial tissue structure, and reduce myocardial cell apoptosis in diabetic rats with MIRI. Meanwhile, the levels of creatine kinase (CK)-MB (CK-MB), lactate dehydrogenase (LDH), and malondialdehyde (MDA) were reduced, while superoxide dismutase (SOD) level was elevated. H9C2 cells were treated with high glucose and oxygen-glucose deprivation/reperfusion (OGD/R) to establish an in vitro model. Capsazepine (CPZ), an antagonist of transient receptor potential vanilloid subtype 1 (TRPV1), and LY294002, an inhibitor of PI3K, were used to treat H9C2 cells in vitro. Apoptosis level and the expression levels of apoptosis-related proteins were measured. It was found that OEA activated TRPV1 and the PI3K/Akt signaling pathway, downregulated the expression levels of apoptosis-related proteins (Bcl-2 and cleaved caspase-3), and ameliorated the apoptosis of H9C2 cells treated with high glucose and OGD/R. This study clarified that OEA, as a TRPV1 agonist, could reduce myocardial cell apoptosis by activating the PI3K/Akt signaling pathway in diabetic rats with MIRI. The findings may provide a theoretical basis for administration of OEA as a potential therapeutic agent into diabetic patients with MIRI.